Kerawanan Konflik Antar Agama dan Politik di Kota Medan - Nazla, Nadiyah Putri (Medan Resource Center, 2024)
This research explores the causes of religious and political conflicts in Medan City and their impacts. Using qualitative methods, data were obtained through interviews with the community and religious leaders. The findings show that since 2019, conflicts have decreased due to increased tolerance, the role of religious leaders, and responsible media. However, the lack of education on politics mixed with religion remains a major challenge. These conflicts can become prolonged if not properly addressed. Good education, high tolerance, and the active role of religious leaders and media are key to maintaining peace. In conclusion, maintaining harmonious relationships among religious communities through mutual respect is important to prevent conflicts. Medan has proven that tolerance and education are essential in preventing religious and political conflicts. Religious leaders play a crucial role in maintaining societal harmony.